Pathos in Guruprasad Mainali's Story 'Naso' - Wagle, Mahendra (Academia Research Journal, 2023)
The present article focuses on the analysis of the storyteller Guru Prasad Mainali's 'Naso Katha' and the study of the use of pathos used in it. Karuna rasa (Pathos) is associated with the rasa theory propounded by Acharya Bharata in the field of Eastern literature and criticism. In Karana rasa, a person or object is vibhava, the pain caused by the related person or object is pathetic feeling. Due to the combination of these, a permanent feeling of grief arises in the karuna rasa and compassion occurs. In this article, the 'Naso' story has been analyzed by referring to this rasa principle and the theoretical recognition of Karuna Rasa. Since 'Naso' story is a social story in which social reality is presented and the suffering and pain caused by the adverse conditions of human life is a social story, its introduction has also been presented and Karuna Rasa used in the story has been searched for. Since the study is qualitative in nature, the story has been analyzed on the basis of theory and a conclusion has been drawn. There are various bases of study in the field of current literature criticism, however, in this study, the selection of Karuna Rasa used in the story 'Naso' is evident because it provides new knowledge to analyze the stories associated with Karuna Rasa based on Eastern literary principles. Narrator Guruprasad Mainali has presented the emotional aspects of Deviraman, Subhadra and Lakshmi's life in the story, but basically, because Lakshmi's death made the story more poignant, the use of karuna rasa has been presented in an effective way in this article.